Catcalling sebagai Bentuk Pelecehan Seksual Traumatis - Saffana Zahro Qila; Rizki Nur Rahmadina; Fadhlin Azizah (Jurnal Mahasiswa Komunikasi Cantrik, 2021)
Catcalling events are now quite familiar, especially in big cities like Yogyakarta, where the population is full of students and college students. Catcalling involves a different experience for everyone. The purpose of this study was to know in depth the experiences and reactions of a person when experiencing catcalling. This research is qualitative research using the phenomenological method. The results of this study indicate that catcalling is a form of verbal sexual harassment and has a negative impact on the victim's life. The informant who became a victim of catcalling chose to remain silent even though it had a deep impact, even to a traumatic experience. Therefore, victims need to voice their interests to get wide attention.Keywords: catcalling, experience, reaction, sexual harassment, verbal communication,